Analysis of the Existence of Environmental Kuznets Curve (EKC) Hypothesis on CO2 Emission, Energy Consumption, and Economic Growth in Indonesia - Rahayuningrum, Silvia Tri (Journal of Economics Research and Social Sciences, 2024)
This research explains environmental issues, in the context of Kuznets' theory that links economic growth, energy consumption and CO2 emissions. The focus of the research is to test the Kuznets Environment Curve (EKC) hypothesis in Indonesia in the period 1990-2019 using time series analysis Vector Error Correction Model (VECM). Research findings show that, both in the long and short term, CO2 emissions and energy consumption have a significant impact, while economic growth has no significant impact. These results indicate that the ECC hypothesis is not supported in Indonesia. Emerging policy implications include the transition to clean energy, sustainable farming and forestry management, waste and pollution control, and increased environmental awareness and education. Faced with the complexity of environmental challenges, the implementation of this policy has become crucial toining a balance between environmental sustainability and economic growth.